Association between dietary inflammatory index and fecal incontinence in American adults: a cross-sectional study from NHANES 2005–2010 - Li, Zhigang; Chen, Xing; Huang, Jiaobao; Cheng, Fei; Wu, Zhao; Yuan, Lebin; Li, Xiaodong; Shen, Wei (Frontiers in Nutrition, 2024)
Objective: Recent studies have demonstrated that the Dietary Inflammatory Index (DII) is relevant to abnormal gut health. However, there is a lack of studies that have explicitly explored the link between fecal incontinence (FI) and DII. The current study aims to explore the relationship between DII and FI.The cross-sectional study enrolled a total of 11,747 participants aged 20-85 from NHANES 2005-2010. Weighted logistic regression was conducted to evaluate the relationship between DII and FI, and restricted cubic spline (RCS) was employed to assess the dose-response relationship between DII and FI. Subgroup analyses were performed according to age, gender, race, and BMI.Result: DII levels were found to be significantly higher in patients with FI than in the normal population (p=0.016). After adjusting for all covariates, DII was found to be significantly correlated with FI(model 2: Q4 vs Q1, OR=1.49, 95%CI: 1.04-2.14, p=0.032, p for trend=0.039). The dose-response curve revealed that there was no nonlinear correlation between DII and FI (p-nonlinear=0.234). Subsequent subgroup analyses uncovered that DII was notably associated with FI in the old (Q4 vs Q1, OR=1.84, 95%CI: 1.07-3.18, p=0.030), female (Q4 vs Q1: OR=2.02, 95%CI: 1.23 -3.33, p=0.008), non-Hispanic white (Q4 vs Q1: OR=1.70, 95%CI: 1.12 -2.59, p=0.015) populations.DII was positively associated with FI, particularly among old, female and non-Hispanic white individuals. Decreasing daily dietary inflammatory levels may be an effective tactic to prevent FI, but the precise mechanisms need to be further investigated.